Growth Performance, Hematological Disorder and Bacterial Challenge on Nile Tilapia (Oreochromis Niloticus) Using Moringa Oleifera Plant Leaf as Feed Supplement (Bangladesh Journal of Zoology, 2020)
Tilapia (Oreochromis niloticus) has been gaining ground in cultivation and sale in Bangladesh but due to price hike of fish feed the culture of this fish faced many challenges. In the present study, the optimal level of dietary moringa (Moringa oleifera) leaf powder was used as feed supplement to determine the growth performances, some selective blood parameters and bacterial load in Nile tilapia, Oreochromis niloticus. Commercial feed with processed moringa leaf at 0g/kg, 100g/kg and 200g/kg diet was used. The diet containing 100g moringa leaf/kg diet resulted in increased weight gain, average daily gain, specific growth rate, condition factor and survival rate. A significant (p